Dakwah Strategy of YukNgaji Community Towards Hallyu Fans through Korean Nuanced Content - Mutiarani, Afifi; Mufidah, Ghina; Yusuf, Maulana (Alhadharah: Jurnal Ilmu Dakwah, 2024)
The Korean-themed content produced by the YukNgaji community represents an innovative approach to da'wah in response to global trends. This study aims to analyze YukNgaji community's da'wah strategies targeting "Hallyu" fans through Korean-themed content. The research employed a literature study approach, gathering qualitative data primarily from YukNgaji's social media and using related articles and websites as secondary sources. YukNgaji's da'wah strategies include using popular Korean terms, Korean-themed da'wah media, Korean language classes, and X-School classes. The strategy applied without any element of coercion and does not judge Korean culture fans, but rather uses Korean culture as an approach to make it easier to understand and attractive to Korean culture fans. This research serves as an initial proposes innovations in spreading da'wah to specific participant segments, including Korean culture fans.